2017
DOI: 10.1177/0093854816688037
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Police Body-Worn Cameras

Abstract: Despite relatively little extant research, efforts to expand the use of body-worn cameras (BWCs) in policing are increasing. Although recent research suggests positive impacts of BWCs on reducing police use-of-force and citizen complaints, little is known about community members’ perceptions of BWCs. The current study examined perceptions of residents of two Florida counties and found a large majority of respondents supported the use of BWCs. Structural equation modeling was utilized to examine factors that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Most of these studies (conducted prior to local police adoption of the technology) offer general public opinions of BWCs and largely speculative commentary regarding the effects of BWCs on public perceptions of police. Specifically, the studies primarily consist of general public perception surveys/interviews (Crow et al, 2017;Edmonton Police Service, 2015;Ellis et al, 2015;Grossmith et al, 2015;James & Southern, 2007;Kerrison, Cobbina, & Bender, 2018;Northeastern University, 2018;ODS Consulting, 2011;Pew Research Center, 2017;Plumlee, 2018 White, 2018;TPS, 2016;YouGov, 2015). These studies demonstrate that the general public tends to support police use of BWCs.…”
Section: Public Perceptions and Bwcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies (conducted prior to local police adoption of the technology) offer general public opinions of BWCs and largely speculative commentary regarding the effects of BWCs on public perceptions of police. Specifically, the studies primarily consist of general public perception surveys/interviews (Crow et al, 2017;Edmonton Police Service, 2015;Ellis et al, 2015;Grossmith et al, 2015;James & Southern, 2007;Kerrison, Cobbina, & Bender, 2018;Northeastern University, 2018;ODS Consulting, 2011;Pew Research Center, 2017;Plumlee, 2018 White, 2018;TPS, 2016;YouGov, 2015). These studies demonstrate that the general public tends to support police use of BWCs.…”
Section: Public Perceptions and Bwcsmentioning
confidence: 99%
“…These studies demonstrate that the general public tends to support police use of BWCs. Explanations for this support typically highlight public perceptions that BWCs will enhance the quality of specific police-public interactions (e.g., in terms of police accountability (TPS, 2016), police misconduct (Northeastern University, 2018), safety (James & Southern, 2007;ODS Consulting, 2011), or officer behavior (Crow et al, 2017). However, these general public perceptions do not necessarily reflect the attitudes and experiences of persons who have had a recent police contact.…”
Section: Public Perceptions and Bwcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worse, White et al (2018) found that officers became less convinced the BWCs influenced citizen behavior the longer they used them. Despite this, nearly 80% of surveyed residents in Florida believed their resident's behavior would improve (Crow et al, 2017).…”
Section: Police-citizen Interactionsmentioning
confidence: 99%
“…Additionally, nearly 90% of residents believed the officer's behavior would improve (Crow et al, 2017). Police officers also believed they would act more professionally towards citizens with the introductions of BWCs.…”
Section: Police-citizen Interactionsmentioning
confidence: 99%